Factors Associated with Obesity in Adults in South East Asia - Putri, Sari M. Ni Ketut; M, Meo. Christina; Saverinus, Suhardin.; M, Halimatunnisa.; Susanti, Inta (International Journal of Psychosocial Rehabilitation, 2020)
Obesity is defined as an abnormal condition with excess fat which is a risk to health. There is a risk of diseases caused by obesity such as type 2 diabetes for adolescents, coronary heart disease, stroke, myocardial infarction, cancer, and even failure to breathe normally while sleeping. The purpose of this research literature is to find factors that are strongly associated with obesity in adults in south east Asia. The literature search strategy identified 647 articles. The PRISMA strategy was used to identify various articles through a database of publications: Scopus, Direct Science, ProQuest, and Springer link. Search keywords used were "Obesity" and "Adult", and articles had to focus on "East Asia" according to the inclusion criteria. Inclusion criteria are 5-year journal limits (2015-2020), document type articles, English language, journals that allow full-text form to be retrieved. Rough calculation of the prevalence of obesity in adults aged 18 years and over in ASEAN countries shows the following levels: Indonesia 28%, Cambodia 50.20%, Laos 20.9% Class I or Class II Obesity, Malaysia 15.4%, Myanmar 8.4%, Singapore 44.1%, Thailand 12.7%, Vietnam 2.53%, Brunei Darussalam 29.5%. In all ASEAN countries rates of obesity are more prevalent in women. Obesity is a health problem in Southeast Asia which can be seen from the increasing prevalence of obesity from year to year in Southeast Asia. In general, the factors that can cause obesity are, sex, age, level of education, physical activity, marital status, history of obesity during childhood, genetics, stress, alcohol consumption and smoking habits, consumption patterns, residence, economic status, sleep habits, culture, social media, and influence of friends.